KAJIAN ONTOLOGI FUNGSIAN WALI MURID DALAM MEMBUAT WATAK ANAK USIA SEKOLAH DASAR - Diah Ayu Sucitra; Muhammad Nurwahidin; Sudjarwo Sudjarwo; Bujang Rahman (Journal of Innovation Research and Knowledge, 2022)
Parents are the first place for a child to get socialization about character education. Children spend children spend more time with their parents at home, so parents have the greatest impact on character development.It can be beneficial to children's lives in the future to provide character education to them at a young age.Using a literature review, the purpose of this study is to examine the ontology study of the role of parents in character development of children.The articles that had been collected on the same subject and had been published between 2017 and 2022 were systematically reviewed for data collection.This study used 15 national journal articles from Google Scholar as reference sources.According to the findings of this study, parents play the most important role in shaping the character of their children.because the child is most at home in the family environment.Children can only succeed if their parents continue to pay attention to them and provide them with direction understand and practice character values ​​well in life everyday.